Dysphagia and tube feeding after stroke are associated with poorer functional and mortality outcomes. Issue 9 (September 2020) - Souza, Juli Thomaz; Ribeiro, Priscila Watson; de Paiva, Sérgio Alberto Rupp; Tanni, Suzana Erico; Minicucci, Marcos Ferreira; Zornoff, Leonardo Antônio Mamede; Polegato, Bertha Furlan; Bazan, Silméia Garcia Zanati; Modolo, Gabriel Pinheiro; Bazan, Rodrigo; Azevedo, Paula Schmidt
Summary: Background & aims: Stroke is the leading cause of disability in adult life. Oropharyngeal dysphagia occurs in 65–90% of patients, and its identification in the acute phase of stroke can prevent complications. The aim of this study was to verify whether oropharyngeal dysphagia during stroke hospitalization is associated with functional capacity, as assessed by the modified Rankin Scale (mRs), and mortality 90 days after stroke. Materials and methods: A prospective cohort study evaluating 201 patients hospitalized in the Stroke Unit was carried out. Dysphagia was evaluated during hospitalization using both a specific protocol to evaluate swallowing biomechanics and the Functional Oral Intake Scale (FOIS), in which FOIS 1–3 reflects tube feeding, 4–5 reflects oral feeding requiring food consistency changes, and 6–7 reflects oral feeding with no changes in food consistency. An mRs≥3 at 90 days after discharge was considered disability. The data were adjusted for the National Institute of Health Stroke Scale score, sex, age, stroke-associated pneumonia, type of stroke, and presence of thrombolysis. The significance level was set at 5%. Results: Of the 201 patients evaluated, 42.8% (86) who had dysphagia were older, had a higher severity of stroke, and pneumonia rate. A FOIS score of 6–7 was a protective factor against disability (mRs≥3) (OR: 0.17; CI: 0.005–0.56; p = 0.004), and tube feeding use at hospital discharge increased the risk of mRs≥3 (OR: 14.97; CI: 2.68–83.65; p = 0.002) and mortality (OR: 9.79; CI: 2.21–43.4; p = 0.003) within 90 days after stroke. Pneumonia was the leading cause of death, however dysphagia and tube feeding at discharge were associated with death from any cause. Conclusion: Dysphagia or tube feeding use at discharge are markers of poor prognosis after the first stroke. Our data suggest the importance of early evaluation of dysphagia and closely monitoring the tube fed patients following stroke.